The Contributions to the History of the Forest Fund' Institutionalization of Bessarabia During the 19-20 Centuries - Cojocaru, Gheorghe; Frangopol, Cătălina (Journal of Danubian Studies and Research, 2023)
During the 19th and 20th centuries, forest' management in historical Bessarabia was carried out through laws, regulations and specialized institutions, with the idea of planning the management of a multi-year forest fund. The administrative measures taken in this regard have undergone changes depending on the events, processes and phenomena that took place in the Russian Empire, in the Romanian space and in its environs.